Combined oral contraceptives: evolution of the relationship benefit/risk - O. S. Alyautdina (Безопасность и риск фармакотерапии, 2018)
Currently, more than 100 million women worldwide use combined oral contraceptives. Risk/benefit ratio of this group of drugs over the half-century history is largely changed in the direction of safety. The factors that increase the safety of this group of drugs, as well as the main risk factors are discussed.